2014
DOI: 10.31018/jans.v6i2.435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and sulphur nutrition on yield parameters and protein composition in soybean [Glycine max (L.) Merrill].

Abstract: ) and combined application of nitrogen (N) and sulphur (S) were investigated. Application of S alone or combined with N significantly increased plant height, number of seeds per pod and total seed yield. Sulphur-containing amino acids viz., methionine and cysteine increased significantly (P≤0.05) by all the treatments in comparison to control and maximum increase of 1.3 fold was observed by urea application. The contents of different protein fractions viz., albumin, globulin and glycinin (a subfraction of glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The increase in these growth parameters may be attributed to the favourable effects of sulphur on N-metabolism, cell division, photosynthetic process and chlorophyll formation, protein structure, vitamins and other structural components resulting in an increased growth stage and development of the plant. Similar conclusions were also reached by Farhad et al (2010), Yadav et al (2013), Sharma et al (2014) and Gill and Sharma, (2017). A higher shoot dry weight and LAI was found in the sulphur level of 20 kg S ha -1 which was at par with 40 kg S ha -1 while the lowest was recorded in the control (Table 1).…”
Section: Effect Of Sulphur On Growth Attributes Of Soybeansupporting
confidence: 87%
“…The increase in these growth parameters may be attributed to the favourable effects of sulphur on N-metabolism, cell division, photosynthetic process and chlorophyll formation, protein structure, vitamins and other structural components resulting in an increased growth stage and development of the plant. Similar conclusions were also reached by Farhad et al (2010), Yadav et al (2013), Sharma et al (2014) and Gill and Sharma, (2017). A higher shoot dry weight and LAI was found in the sulphur level of 20 kg S ha -1 which was at par with 40 kg S ha -1 while the lowest was recorded in the control (Table 1).…”
Section: Effect Of Sulphur On Growth Attributes Of Soybeansupporting
confidence: 87%
“…On the contrary globulin fraction did not show any increase. The results are in accordance to the findings of Sharma and Sharma (2014); Sharma et al, (2013).…”
Section: Resultssupporting
confidence: 82%
“…In addition, modifies seed protein composition by decreasing the abundance of storage proteins with the highest content of S-containing amino acid, while increasing the level of S-poor globulins (Zuber et al, 2013). Similarly, Sharma and Sharma (2014) also reported that a significant increase in Scontaining amino acids such as methionine and cysteine obtained by combined application of N and S for soybean. Therefore, the results of this study indicated that S fertilization is required to improve N-use efficiency and thereby maintaining protein quality (Fismes et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…Because S is a main component of the amino acids methionine, cysteine, and cystine, coenzymes, thioredoxine and sulfolipids and hence improves protein quality (Jemal et al, 2005). Sharma and Sharma (2014) also reported S-containing amino acids such as methionine and cysteine increased significantly by combined application of N and S and indicated improvement in soybean nutritional value. This is because N and S are both involved in plant protein synthesis, a process that may determines yield of crops (Habtemicheal et al, 2013).…”
Section: Introductionmentioning
confidence: 87%